Natural Environment Based Science Learning to Improve Critical Thinking and Creativity Skills in Early Childhood - Roostin, Erna; Ajeng Sri Hikmayani (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2026)
Science learning in early childhood education is still predominantly instructional and teacher-centered, resulting in limited meaningful learning experiences for children. This condition contributes to the low levels of critical thinking and creativity, which are essential 21st-century competencies. This study aimed to improve early childhood critical thinking and creativity through the implementation of nature- based science learning. The study used a two-cycle implementation of the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model; each cycle had the following steps: preparation; action; observation; and reflection. The research subjects were 15 children aged 4–6 years at TK Darul Quran, Sumedang Regency. Data were collected through observation, documentation, and reflective notes using observation sheets to assess children's critical thinking and creativity skills. Data analysis was conducted using descriptive quantitative and qualitative approaches. The results showed that children's critical thinking skills increased from 10% in the pre-cycle to 60% in Cycle I and 90% in Cycle II. Similarly, creativity skills improved from 20% to 65% and 92%, respectively. These findings indicate that nature-based science learning can in enhancing critical thinking and creativity in early childhood education.